Neuraminidase Inhibition And In Vitro Anti Influenza A (H1n1) Activities Of Brucea Javanica (L.) Merr - Purwitasari, Neny (2013)
The outbreak of influenza A viruses (H1N1 and H5N1) has raised a global concern on the future risk of a pandemic. Oseltamivir, the current neuraminidase inhibitor, could not meet the demand if there is a major outbreak. Thus, there is a need to find alternative treatment for influenza A. Our molecular docking work on neuraminidase has led to the selection of plant to be studied, Brucea javanica (L.) Merr (Simaroubaceae). The objectives of this study were to determine the neuraminidase inhibition and in vitro influenza A antiviral activities of Brucea javanica (L.) Merr. In order to obtain information about the active compounds from this plant, the dried fruits were extracted using methanol, and fractionated using n-hexane, ethyl acetate and nbutanol. One compound was isolated from ethyl acetate fraction, identified as β- sitosterol 3-O-β-D-glucopyranoside or daucosterol. Crude methanol extract, n-hexane fraction, ethyl acetate fraction, n-butanol fraction as well as daucosterol were subjected to the neuraminidase inhibition assay (MUNANA Assay) against Clostridium perfringens, H5N1 and H1N1 neuraminidase enzymes and in vitro antiviral assay against A/Indonesia/Unair/2011 (H1N1) virus on MDCK cells. The reduction of hemagglutinin titre was performed in hemagglutination assay (HA Assay), while the reduction of virus infectious titre was performed in Half Tissue Culture Infectious Dose (TCID50) assay.